2013
DOI: 10.1111/wrr.12020
|View full text |Cite
|
Sign up to set email alerts
|

Randomized controlled trial on collagen/oxidized regenerated cellulose/silver treatment

Abstract: Collagen/oxidized regenerated cellulose (ORC)/silver therapy has been designed to facilitate wound healing by normalizing the microenvironment and correcting biochemical imbalances in chronic wounds. The aim of this study was to compare collagen/ORC/silver therapy to control (standard treatment). Patients with diabetic foot ulcers were randomized to either collagen/ORC/silver (24) or control treatment (15). Wound area measurements and wound fluid samples were taken weekly. Protease levels were measured in woun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
93
0
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 81 publications
(96 citation statements)
references
References 35 publications
1
93
0
2
Order By: Relevance
“…However, due to its acidic pH, ORC is resistant to bacterial infection,24 and several studies have found that ORC actually prevents infection 2526. In the current study, none of the animals exhibited significant preoperative to postoperative changes in WBC and CRP values, the presence of which may suggest infection.…”
Section: Discussionmentioning
confidence: 99%
“…However, due to its acidic pH, ORC is resistant to bacterial infection,24 and several studies have found that ORC actually prevents infection 2526. In the current study, none of the animals exhibited significant preoperative to postoperative changes in WBC and CRP values, the presence of which may suggest infection.…”
Section: Discussionmentioning
confidence: 99%
“…70 Clinical studies have shown a significant reduction of MMP, elastase, and gelatinase content in diabetic foot ulcers with either ORC/collagen or ORC/collagen/silver. 73,74 Although not proof of cause and effect, when combined with the evidence that elevated inflammatory protease activity in the wound is a robust indicator of nonhealing, 75 the portfolio of studies strongly supports the fact that ORC/ collagen will modulate the chronic wound microenvironment.…”
Section: Clinical Application Of Collagen-based Biomaterialsmentioning
confidence: 99%
“…Oxidized regenerated cellulose/collagen matrix (ORC/collagen matrix) has been reported to improve the wound microenvironment by adsorbing wound exudate and retaining proteases within the dressing structure. [7][8][9][10][11][12][13] A randomized controlled trial demonstrated the superiority on modulating proteases of a wound dressing based on the LipidoColloid Technology, impregnated with a NanoOligo Saccharide Factor compared with an ORC/ collagen matrix. 14 A systematic review of the clinical evidence on protease-modulating dressing and researches that compare these devices would be useful in providing an overview of the appropriate treatment to achieve optimal healing for chronic wounds.…”
Section: Discussionmentioning
confidence: 99%
“…[7][8][9][10][11][12][13][14] Among these, negative pressure therapy (NPT) plays an interesting role. NPT is a noninvasive therapy system that applies controlled negative pressure using a vacuum-assisted closure device.…”
Section: Introductionmentioning
confidence: 99%